Cognitive Function and Digital Device Use in Older Adults Attending a Memory Clinic. (April 2019) - Wu, Ya-Huei; Lewis, Manon; Rigaud, Anne-Sophie
This study investigated cognitive function in relation to the use of a computer and a touchscreen device among older adults attending a memory clinic. The entire sample ( n = 323) was categorized into four profiles, according to the frequency of digital device use (either daily or non-daily usage). Results showed that on a daily basis, 26% of the sample used both a computer and a touchscreen device, 26.9% used only a computer, 7.1% used only a touchscreen device, and 39.9% used neither type of digital device. There were significant group differences on age, education, and clinical diagnosis ( p < .001). Non-daily users of digital devices had significantly lower performance, compared with daily users of both types of digital device, on measures of global cognitive function, processing speed, short-term memory, and several components of executive function ( p < .001). Falling behind with regard to the use of digital devices might reflect underlying poor cognitive capacities.